Faktor Risiko Kelelahan Kerja pada Pekerja Satuan Pengamanan (SATPAM) : Systematic Literature Review - Ayu, Karisma; Djamalus , Hendra (Syntax Corporation, 2025)
The state of tiredness, fatigue, or drowsiness that arises as a result of excessive activity is referred to as fatigue. Work fatigue is one of the problems that is often experienced by Security Unit (Satpam) workers and can have an impact on decreased performance and increased risk of work accidents. This study aims to identify the main risk factors that contribute to occupational fatigue in security guards in Indonesia. The method used was a systematic literature review with the PRISMA approach, with the selection of journals published between 2020-2025. The results showed that 67.3% of security unit workers experienced job fatigue. Age and work factors such as work shifts, physical workload, mental workload and long work duration have a significant relationship with the level of fatigue. Night shifts were found to be the main factor that increased the risk of fatigue due to circadian rhythm disruption and lack of optimal rest time. To reduce fatigue in security guards, a more balanced work schedule, adequate rest facilities, and education on fatigue management are needed.